Dissimilar Laser Welding of AISI 321 and AISI 1010 - Stanciu, Elena Manuela; Pascu, Alexandru; Tierean, Mircea Horia; Roata, Ionut Claudiu; Voiculescu, Ionelia; Hulka, Iosif; Croitoru, Catalin (Mechanical Engineering Faculty in Slavonski Brod, 2018)
This paper presents the dissimilar laser welding of AISI 321 stainless steel and AISI 1010 carbon steel thin sheets in butt joint geometry using a 1 kW diode laser. Influence of the welding speed on the geometry and microstructure of the joints is discussed. Structural characterisation of the welds is realised through optical, electron microscopy and EDS analysis, observing distinct mixed and unmixed areas in the weld bead because of the high cooling rate. The weld bead presents an austenitic-martensitic-ferrite structure, characterized by austenitic twin grains with ferrite particles precipitated on grain boundaries, and islands comprising a ferrite-martensite structure. Chromium and nickel migration in the weld bead area was observed. Good tensile behaviour of the dissimilar joints was obtained, as all the specimen failure occurs far-off the weld zone.
Keywords: dissimilar welding; laser; microhardness; stainless steel; tensile behaviour